Β-Amyloid promotes platelet activation and activated platelets act as bridge between risk factors and Alzheimer's disease. (October 2022) - Li, Tao-Ran; Liu, Feng-Qi
Abstract: Alzheimer's disease (AD) is an evolving challenge that places an enormous burden on families and society. The presence of obvious brain β-amyloid (Aβ) deposition is a premise to diagnose AD, which induces the subsequent tau hyperphosphorylation and neurodegeneration. Platelets are the primary source of circulating amyloid precursor protein (APP). Upon activation, they can secrete significant amounts of Aβ into the blood, which can be actively transported to the brain across the blood-brain barrier and promote amyloid deposition. In this review, we summarized the changes in the platelet APP metabolic pathway in patients with AD and further comprehensively explored the targets and downstream events of Aβ-activated platelets. In addition, we attempted to clarify whether patients with AD are in a state of general platelet activation, with inconsistent results. Considering the increasingly evident bidirectional relationship between AD and vascular events, we speculate that the AD pathology alone seems to be insufficient to induce the general activation of platelets; however, the intervention of third-party factors, such as atherosclerosis, exposes the extracellular matrix and leads to platelet activation, further promoting AD progression. Therefore, we proposed a framework in which the relationship between platelets and AD is indirect and mediated by vascular factors. Therapies targeting platelets and interventions for vascular risk factors are likely to contribute to the prevention and treatment of AD. Highlights: In patients with AD, the metabolism of platelet APP changes to amyloidogenic pathway. It is not sure whether patients with AD are in a state of platelet activation. Aβ promotes platelet activation via multiple receptors and downstream events. Platelet activation indirectly related to AD and bridged by vascular risk factors.